Unemployment in Kazakhstan and identifying its causes (Journal of Economic Research & Business Administration, 2015)
The article considers the main problems in the labor market .In particular, we studied the main causes of unemployment in theKazakhstan. Message from the President "Socio-economicmodernizatsiya- main vector of development of Kazakhstan "considered to be one of the solutions to the problem of employment .He noted that for the realization of its important role of the Governmentand society.
Keywords: Unemployment; labor market issues